Impaired Binocular Depth Perception in First-Episode Drug-Naive Patients With Schizophrenia - Wang, Zhengchun; Yu, Zhipeng; Pan, Zhichao; Zhao, Keyu; Zhao, Qiqi; Zhou, Dongsheng; Shen, Hao-Wei; Wu, Xiangping (Frontiers in Psychology, 2018)
Binocular depth perception (BDP) is one of the most demanding visual function that involves both dorsal and ventral visual information streams. Substantial research has been conducted on the disruption of BDP in patients with schizophrenia. However, research on first-episode and drug-naive patients with schizophrenia (FEDN) is limited. To assess the BDP of schizophrenia patients while controlling for the effects of antipsychotics and the duration of illness. We investigated BDP in patients with schizophrenia via the Titmus Stereopsis Test in this study, by matching the patients into three groups: FEDN (n = 17), long duration of illness and medicine treatment (LDMT) (n = 31) and the healthy control group (n = 40). Results showed that both the FEDN (mean = 1.71, 95% confidence interval [CI]: [1.57, 1.84]) and LDMT (1.73, 95% CI: [1.66, 1.81] patients displayed a significant decline (p = 0.01, Cohen’s d = 0.67, p = 0.001, Cohen’s d = 0.92, respectively) in depth perception compared to the healthy control (1.55, 95% CI: [1.48, 1.61]) group. Additionally, there were no significant differences (p = 0.68, Cohen’s d = 0.11) between the FEDN and LDMT groups, and no correlation (Pearson r = -0.16, p = 0.38, R2 = 0.03) was observed between the duration of illness and impaired BDP in the LDMT group. The proportion of individuals with stereopsis detection in either FEDN (12/17) or LDMT (26/31) groups under stereo threshold 63 arc seconds ("), were significantly lower (Pearson χ2 = 6.29, p = 0.043, φ_c= 0.27) compared to the healthy control group (38/40). Significant difference in stereopsis detection also occurred at 50" (Pearson χ2 = 12.31, p = 0.001, φ_c= 0.37), 40" (Pearson χ2 = 12.38, p = 0.002, φ_c= 0.38), 32" (Pearson χ2 = 6.69, p = 0.035, φ_c= 0.28), 25" (Pearson χ2 = 14.82, p = 0.001, φ_c= 0.41) and 20" (Pearson χ2 = 6.73, p = 0.034, φ_c= 0.28) between the three groups. These findings showed a moderately strong association between schizophrenia and defective stereopsis.